Response of garlic (Allium sativum L.) to phosphorous and sulphur application in acid alfisol of Meghalaya - Patiram Patiram, B Majumdar, M S Venkatesh, Kailash Kumar (Journal of Spices and Aromatic Crops, 2003)
In a field experiment with three levels of P (0, 50 and 100 kg P20 S ha-1) and four levels of 5 (0, 10, 15 and 20 kg 5 ha-1) on a P and 5 deficient Typic HapludalJ of Meghalaya, the bulb and straw yield, nutrient uptake and protein content of garlic increased significantly with increasing levels of P and S application. The available P and 5 content in post harvest soil increased significantly with P and S application. The interaction effects of P and S were significant for bulb yield, N, P and S uptake and available P and S in post harvest soil and their highest values were recorded with Pmo 520 treatment combination. P use efficiency increased with 5 levels and was higher at P 50 as compared to Pwo level. S use efficiency increased with increasing levels of P and S. Maximum P and S use efficiency were recorded with P 50S20 and P 100S20 treatment combinations, respectively.